Disclosure Of Final Stadium Patients' Diagnosis Review From Law And Bioethics In Indonesia - Arsyzilma Hakiim; Fifik Wiryani (Universitas Muhammadiyah Malang, 2022)
The relationship between doctor-patient rights and obligations, especially in hospitals, cannot be separated from conflicts or disagreements. These conflicts usually occur in special conditions that cause dilemmas in decision-making by doctors. Disclosure of the truth of the diagnosis in terminal patients or those suffering from end-stage disease is an ethical and legal issue that often occurs in health services. Problems occur, where on the one hand if the doctor tells the truth (reveals the truth) regarding the diagnosis/disease and on the other hand the doctor is worried that revealing the truth will have an impact that can worsen the patient's condition such as making the patient more depressed so that the patient can refuse further treatment. . But on the other hand, patients have the right to know information related to their illness. This research was conducted with a normative review approach. The results of this study found that disclosure of the truth about the end-stage disease can cause disturbances in psychological aspects and can potentially affect the patient's quality of life. The legal approach in disclosing the truth of end-stage disease through Law Number 36 of 2009 concerning health, Law Number 44 of 2009 concerning hospitals, and Law Number 29 of 2004 concerning medical practice is not fully the basis for the implementation of doctors in conveying the truth. Therefore, the bioethical aspect approach in this case through the principles of non-maleficence and respect for autonomy, truth disclosure can be done ethically and can minimize the negative impact of truth disclosure.